Total tau in cerebrospinal fluid detects treatment responders among spinal muscular atrophy types 1–3 patients treated with nusinersen - Šimić, Goran; Vukić, Vana; Babić, Marija; Banović, Maria; Berečić, Ivana; Španić, Ena; Zubčić, Klara; Golubić, Anja Tea; Barišić Kutija, Marija; Merkler Šorgić, Ana; Vogrinc, Željka; Lehman, Ivan; et al. (CNS neuroscience & therapeutics, 2024)
Aims Considering the substantial variability in treatment response across patients with spinal muscular atrophy (SMA), reliable markers for monitoring response to therapy and predicting treatment responders need to be identified. The study aimed to determine if measured concentrations of disease biomarkers (total tau protein, neurofilament light chain, and S100B protein) correlate with the duration of nusinersen treatment and with scores obtained using functional scales for the assessment of motor abilities. Methods A total of 30 subjects with SMA treated with nusinersen between 2017 and 2021 at the Department of Pediatrics, University Hospital Centre Zagreb, Croatia, were included in this study. Cerebrospinal fluid (CSF) samples were collected by lumbar puncture prior to intrathecal application of nusinersen. Protein concentrations in CSF samples were determined by enzyme‐linked immunosorbent assay in 26 subjects. The motor functions were assessed using functional motor scales. Results The main finding was significantly decreased total tau correlating with the number of nusinersen doses and motor improvement in the first 18–24 months of treatment (in all SMA patients and SMA type 1 patients). Neurofilament light chain and S100B were not significantly changed after administration of nusinersen. Conclusions The measurement of total tau concentration in CSF is a reliable index for monitoring the biomarker and clinical response to nusinersen therapy in patients with SMA. In this study, we performed a follow‐up study of 26 spinal muscular atrophy types 1–3 patients treated with nusinersen between 2017 and 2021 to determine if measured concentrations of total tau, neurofilament light chain, and S100B proteins in cerebrospinal fluid correlate with the duration of nusinersen treatment and with scores obtained using functional scales of motor abilities. The main finding was significantly decreased total tau protein correlating with the number of nusinersen doses and motor improvement in the first 18–24 months of treatment. Neurofilament light chain and S100B were not significantly changed after administration of nusinersen.